2020
DOI: 10.1021/acscentsci.0c01130
|View full text |Cite
|
Sign up to set email alerts
|

Metal@Zeolite Hybrid Materials for Catalysis

Abstract: The fixation of metal nanoparticles into zeolite crystals has emerged as a new series of heterogeneous catalysts, giving performances that steadily outperform the generally supported catalysts in many important reactions. In this outlook, we define different noble metal-in-zeolite structures (metal@zeolite) according to the size of the nanoparticles and their relative location to the micropores. The metal species within the micropores and those larger than the micropores are denoted as encapsulated and fixed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
122
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 190 publications
(123 citation statements)
references
References 126 publications
(274 reference statements)
1
122
0
Order By: Relevance
“…For the foreseeable future, carbon-based fuels, such as natural gas, petroleum, and biomass, will continue to be a significant part of our energy infrastructure, and interfacially engineered heterogeneous catalytic materials relying on transition metal (TM) species will continue to play a critical role in meeting our daily energy needs. [1][2][3][4] It has been demonstrated that once supported or confined, TMs, their oxide, carbide and nitrides particles exhibit promising performance with high activity and selectivity in selective conversion of methane, [5][6][7][8] low-temperature CO conversion, 9,10 selective hydrogenation/dehydrogenation, [11][12][13][14] bio-oil conversion and upgrading, [15][16][17][18] and water-gas shift reaction 19,20 . Existing literature on heterogeneous catalytic materials primarily emphasize their outstanding performance and complexity in kinetics and reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…For the foreseeable future, carbon-based fuels, such as natural gas, petroleum, and biomass, will continue to be a significant part of our energy infrastructure, and interfacially engineered heterogeneous catalytic materials relying on transition metal (TM) species will continue to play a critical role in meeting our daily energy needs. [1][2][3][4] It has been demonstrated that once supported or confined, TMs, their oxide, carbide and nitrides particles exhibit promising performance with high activity and selectivity in selective conversion of methane, [5][6][7][8] low-temperature CO conversion, 9,10 selective hydrogenation/dehydrogenation, [11][12][13][14] bio-oil conversion and upgrading, [15][16][17][18] and water-gas shift reaction 19,20 . Existing literature on heterogeneous catalytic materials primarily emphasize their outstanding performance and complexity in kinetics and reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the conventional impregnation cannot guarantee the metal precursor enter into the zeolite pores through subnanometric pore window, and a substantial of metal species will locate on the zeolite external surface, showing unsatisfied stability during PDH reaction. Recently, the encapsulation of metal species within zeolites (M@zeolite) by ligand‐assistance in situ crystallization strategy has been frequently reported, which exhibits various advantages for light hydrocarbon catalytic reactions 12–17 . For example, Gong and the colleagues reported the encapsulation of ultrasmall Pd clusters into sodalite zeolites 12 .…”
Section: Introductionmentioning
confidence: 99%
“…For the foreseeable future, carbon-based fuels, such as natural gas, petroleum, coal, and biomass, will continue to be a significant part of our energy infrastructure, and interfacially engineered heterogeneous catalytic materials relying on transition metal (TM) species will continue to play a critical role in meeting our daily energy needs. [1][2][3][4] It has been demonstrated that supported or confined TMs, their oxide (TMO), carbide (TMC), and nitride (TMN) particles exhibit promising performance with high activity and selectivity in selective conversion of methane, [5][6][7][8] low-temperature CO conversion, 9,10 selective hydrogenation/dehydrogenation, [11][12][13][14] bio-oil conversion and upgrading, [15][16][17][18] and water-gas shift reaction. 19,20 Existing literature on heterogeneous catalytic materials primarily emphasize their outstanding performance and complexity in kinetics and reaction mechanisms.…”
Section: Introductionmentioning
confidence: 99%